Bringing morality back in: Accounting as moral interlocutor in reflective equilibrium processes - Kraus, Kalle; Mikes, Anette; Véliz, Carissa (Accounting, Organizations and Society, 2024)
The situations in which accounting is practiced raise moral concerns about customer and employee safety, community welfare, environmental sustainability, and human rights. Traditional accounting practices, such as budgets and performance measurement systems, have been widely regarded as ‘crowding out morality’ by objectifying the people affected by a firm's actions. In two North American utilities, we observed a stepwise structured process of moral reflection (which we identify as an instance of Rawls's reflective equilibrium approach), in which accounting, in the form of the risk appetite radar, helped guide executive decision making informed by moral principles. We develop two dimensions of accounting's role as ‘moral interlocutor’: enabling organizational value consensus and organizational value coherence. We identify three features of the observed accounting practice that enable it to act as moral interlocutor: subjectification rather than objectification of potential victims of the firm's actions; de-monetization, that is, considering trade-offs in terms of multiple organizational values, not only in terms of cost; and visualization of the organizations' moral principles on value priorities and how they are shaped by organizational decision making and action. The accounting visualizations did not only enable executives' reflection on rights and wrongs, but also triggered a fuller and richer moral vocabulary that was used for complex decision making involving, for instance, automation and the risk of suicides.